The state of anatomical donation programs amidst the SARS‐CoV‐2 (Covid‐19) pandemic. Issue 6 (3rd June 2021) - McCumber, Travis L.; Latacha, Kimberly S.; Lomneth, Carol S.
Abstract: The inclusion of human body dissection in anatomical science curricula has been described as a critical educational experience for the mastery of anatomical structures and concepts. To ensure that body donors are ethically acquired and suitable for anatomy education, Anatomical Donation Programs (ADPs) are tasked with the responsibility of acquiring body donors for basic and clinical science curricula. Considering the personal and institutional impact of SARS‐CoV‐2, a national survey was conducted to examine the current effect of the pandemic on ADP protocols, body donation, and the sustainability of ADPs in the United States (U.S.). Eighty‐nine U.S. ADPs were identified and contacted for optional participation in a survey to assess the impact of the SARS‐CoV‐2 pandemic on their programs. Survey data were collected and managed using REDCap electronic data capture tools. Thirty‐six ADPs (40.5% response rate) from the nine U.S. Divisions are represented in the survey results. Data were collected on ADP descriptions and demographics, SARS‐CoV‐2 impact on ADPs and protocols, and body donation and ADP sustainability. Almost all ADPs reported that the pandemic has affected their ADP operations in some way; however, the sustainability for the majority of ADPs appears likely and donor availability remains stable due to a proportional decrease in body donations and body donor requests. As the long‐term impact on ADPs has yet to be determined, the authors plan to reevaluate the lasting impact of the SARS‐CoV‐2 pandemic on body donation, ADP sustainability, and anatomical science education throughout the year 2021.